Ghazar P'arpets'i history of the Armenians - Ghazar, Pʻarpetsʻi, 5. yy. ([Dandenong South, Victoria])
2 cilt (1. c. xx, 357 sayfa ; 2. c. xviii, 268 sayfa)
Keywords: “This set contains both volumes of the History of the Armenians by Ghazar P'arpec'i (Parpetsi). This work is one of the gems of the Golden Age of Armenian literature and is an important part of Sophene’s Dual Language Series. In this series, we aim to make the most important works of ancient Armenian literature accessible to the broadest possible audience by placing the original Armenian text on the left-hand side and the corresponding English translation on the right-hand side. Ghazar P'arpec'i's History of the Armenians was written at the end of the fifth or beginning of the sixth century. The first book of this three-book work begins with information concerning the division of Armenia between the Byzantine and Sasanian empires (in 387), and describes the invention of the Armenian alphabet and the abolition of the monarchy in the Iranian-controlled eastern sector (428) to the death of Catholicos Sahak (439). Book II describes the anti-Iranian Armenian uprising of 450/451 (the battle of Awarayr) led by Vardan Mamikonean, while Book III describes another anti-Iranian uprising led by Vardan's nephew, Vahan Mamikonean, and known as the Vahaneanc' (481-84). Volume I contains Books I and II, while Volume II contains Book III“ --